Evaluation of anatomic variations of the paranasal sinuses by computed tomography - Can Alper Çağıcı; Haluk Yavuz; Nabi Erkan; Babür Akkuzu; Levent Özlüoğlu (Turkish Archives of Otorhinolaryngology, 2006)

(untitled)
Objectives: Our goal in this study, to estimate the incidence of each paranasal sinus anatomic variation in the same population and by this way the incidence levels of each variation compare with each other objectively.Methods: One-hundred paranasal sinus tomography, which had been taken on the dates between January and February 2003, were evaluated retrospectively for the paranasal sinus anatomic variations.Results: The pneumatization of the superior concha was detected on the 50%, concha bullosa on the 69%, the paradoxical middle concha on the 12%, accessory maxillary sinus ostium on the 17%, agger nasi cell on the 83%, Haller cell on the 19%, the medial deviation of the uncinate process on the 12%, the lateral deviation of the uncinate process on the 4%, the pneumatization of the uncinate process on the 17%, the hypoplasia of the uncinate process on the 2%, the pneumatization of the crista galli on the 15%, septum deviation on the 52%, the pneumatization of the nasal septum on the 57%, asymmetric septum of the sphenoid sinus on the 79%, multiseptation of the sphenoid sinus on the 60%, the pneumatization of the anterior clinoid process on the 28% and the pneumatization of the pterygoid process on the 40% of the evaluated tomographies.Conclusion: The incidence value of the paranasal sinus anatomic variations is one of the highlights for the examiner during the evaluation of the paranasal sinus tomographies. However these incidence values show much or less differences between the studies, which were previously published in the literature and also including our study. In conclusion, each patient should be evaluated individually and all paranasal sinus tomographies should be examined for each anatomic variation even if its incidence is low.